A MULTIDIMENSIONAL APPROACH TO PREVENTING RADICALISM THROUGH PANCASILA IDEOLOGICAL RESILIENCE IN THE VUCA ERA - Khulfi Khalwani; Shaghi Ratu Sa’bani; Guntur Eko Saputro (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2025)
This study examines the strategy to prevent radicalism through strengthening the resilience of the Pancasila ideology in the VUCA era which is characterized by volatility, uncertainty, complexity, and ambiguity. Using the Systematic Literature Review method of sixty-four scientific articles and a number of relevant supporting sources, this study maps four main clusters that affect the effectiveness of radicalism prevention, namely ideological resilience, educational interventions, digital literacy, and multi-stakeholder collaboration. The findings show that the prevention of radicalism requires a shift from a repressive approach to a soft power strategy that emphasizes holistic Pancasila education, strengthening critical capacity in the digital space, and developing an inclusive and adaptive social ecosystem. In addition, this study emphasizes the importance of epistemic vigilance, civic participation, and the role of families and religious institutions in building the ideological fortress of society. This study provides a comprehensive conceptual framework for strengthening the resilience of the Pancasila ideology and offers policy directions for the government, educators, and community organizations. Although limited to a literature analysis, the results of this study serve as an important basis for empirical studies and advanced policy formulation.